Faith, Love, and "a Sea of Comfort": Luther's Lectures and Sermons on 1 John - Lohrmann, Martin J. (Word & world, 2021)
In 1527, in the midst of pandemic, sorrow, and controversy, Martin Luther lectured on I John. In such a time of trial Luther found in the words of this epistle a message of consolation and hope meant to encourage. He showed his listeners a Christian path, a "middle way," to release them from sin and despair and to free them for lives of love of God and neighbor.